Digenic Heterozygous Mutations in SLC34A3 and SLC34A1 Cause Dominant Hypophosphatemic Rickets with Hypercalciuria - Gordon, Rebecca J (J Clin Endocrinol Metab, 2020)
CONTEXT: Hypophosphatemia and metabolic bone disease are associated with hereditary hypophosphatemic rickets with hypercalciuria (HHRH) due to biallelic mutations of SLC34A3 encoding the NPT2C sodium-phosphate cotransporter and nephrolithiasis/osteoporosis, hypophosphatemic 1 (NPHLOP1) due to monoallelic mutations in SLC34A1 encoding the NPT2A sodium-phosphate cotransporter. OBJECTIVE: To identify a genetic cause of apparent dominant transmission of HHRH. DESIGN AND SETTING: Retrospective and prospective analysis of clinical and molecular characteristics of patients studied in 2 academic medical centers. METHODS: We recruited 4 affected and 3 unaffected members of a 4-generation family in which the proband presented with apparent HHRH. We performed clinical examinations, biochemical and radiological analyses, and molecular studies of genomic DNA. RESULTS: The proband and her affected sister and mother carried pathogenic heterozygous mutations in 2 related genes, SLC34A1 (exon 13, c.1535G>A; p.R512H) and SLC34A3 (exon 13, c.1561dupC; L521Pfs*72). The proband and her affected sister inherited both gene mutations from their mother, while their clinically less affected brother, father, and paternal grandmother carried only the SLC34A3 mutation. Renal phosphate-wasting exhibited both a gene dosage–effect and an age-dependent attenuation of severity. CONCLUSIONS: We describe a kindred with autosomal dominant hypophosphatemic rickets in which whole exome analysis identified digenic heterozygous mutations in SLC34A1 and SLC34A3. Subjects with both mutations were more severely affected than subjects carrying only one mutation. These findings highlight the challenges of assigning causality to plausible genetic variants in the next generation sequencing era.